Telecommunications use in education to provide interactive visual feedback on automatically graded essays - Williams, Robert; Dreher, Heinz (Communication Economics and Electronic Markets Research Centre, 2005)
This paper discusses the idea of automatic computer marking of assignments and linking learners and teachers to virtually immediately available interactive visualizations of the assessment results. MarkIT is an Automatic Essay Grading System being developed by the authors, and for which they have a provisional patent application filed. It makes use of proprietary algorithms using Natural Language Processing techniques. At its heart is an English language thesaurus used under license from Macquarie Dictionary Pty Ltd. MarkIT provides, in addition to a numerical essay score, comprehensive visual and textual feedback on essay content to enable the teacher to discuss the strengths and weaknesses of the essay, and areas for improvement with the student within a very short time of the essay being submitted for assessment. An example of MarkIT system functionality and performance is presented. Further system development possibilities are presented to permit upload, grading and interactive feedback provision via the Web or wireless networks.